Intermittency of vector fields and natural random number generators - Kalinin, A.O.; Sokoloff, D.D. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2016)
Growth of Jacobi fields on geodesic lines over a 2D manifold with Gaussian curvature as a random process is considered. We study various «natural» random number generators on the basis of the hypothesis that the decimals of irrational numbers are randomly distributed.